Mixed T cell CHIMERISM in bone marrow at day+30 after allogeneic stem cell transplantation: Correlation with acute GVHD grades III–IV and no impact on relapse and overall survival. (27th April 2022) - Guidotti, Samantha; Bassi, Simona; Rossi, Angela; Borotti, Elena; Cortellazzi, Pilade; Ferrarese, Diego; Ronda, Elena; Scarpa, Alice; Schiro, Alice; Merli, Francesco; Prezioso, Lucia; Bonifazi, Francesca; et al.
Abstract: Objectives: Early chimerism analysis is important to assess engraftment in allogeneic hematopoietic stem cell transplantations. Methods: We retrospectively investigated the impact of T‐cell chimerism at day 30 in bone marrow on acute graft‐versus‐host disease (aGVHD), relapse, and overall survival in 142 adult allo‐transplanted patients. Results: The majority of patients (89%) received myeloablative conditioning and 90% have undergone T‐cell replete donor graft. At day 30, 103 patients showed T‐complete chimerism with prevalence in haploidentical transplants, whereas 39 cases had CD3+ mixed chimerism, including 30 patients transplanted with HLA identical donors, and 21 with T‐cell donors<90%. T‐cell chimerism at day 30 was weakly inversely related to aGVHD grades II–IV ( p = .078) with no cases of grades III–IV aGVHD in patients with CD3+ <95%. Mixed T‐cell chimerism did not impact on relapse ( p = .448) and five of the seven patients who relapsed had T‐cell chimerism ≤90%. Older age and active disease at transplant had a statistically significant negative effect on overall survival ( p = .01 and p = .0001, respectively), whereas mixed CD3+ chimerism did not. Conclusions: T lymphocyte chimerism analysis at day +30 in bone marrow could identify allo‐transplanted patients at major risk of aGVHD grades III–IV (CD3+ donors >95%) mainly post‐myeloablative conditioning regimen.